SELF-WORTH AND THE LIFE EXPERIENCES OF HOMELESS PEOPLE - Poškaitė, Rūta; Petružytė, Donata (Socialinė teorija, empirija, politika ir praktika, 2018)
Two decades ago, the importance of research on homelessness was noted. The collected information about homeless lifestyle, psychological health and experience help to reveal the dynamics of homelessness. The research also helps in expanding and encouraging the prevention system, the need for help and in noticing the risk groups.Researchers of homelessness in Lithuania analyze the general sociodemography of homeless persons, their individual experiences, causes, types and forms of homelessness. The self-worth of homeless people is not studied widely in Lithuania. Therefore, the aim of this paper is to reveal the link between homeless life experience and self-worth.In the first part of this article, we reveal the conception of self-worth and the various aspects of self-worth of homeless people. In the second part of this article, we present the research results. The main objectives of this work were to determine the links between self-worth and social-demographical characteristics, social relations and homeless experience. The survey was carried out in temporary shelters and day centers of the homeless in Vilnius and Panevėžys. For this study, 112 homeless people were surveyed. To achieve the aims of this study, a quantitative method was applied and a questionnaire-based survey was conducted. The Rosenberg scale was used in order to measure the self-worth of homeless people. The results of self-worth were compared with the characteristics of the homeless lifestyle.The research revealed the general characteristics of homeless people and showed that homeless people’s self-worth is mostly either low or medium. There are negative correlations among education, alcohol use, health and self-worth. Lower self-worth was noticed in those who had lower education, bad health and frequently consumed alcohol. The research also revealed that criminal experience negatively affects homeless self-worth.
Keywords: homelessness; homeless people; self-worth